Implementation of Data Synchronization Mechanism in Virtual Desktop Infrastructure - Chiao-Tung Yang; Jheng-Yue Li; Cai-Jin Chen; Chun-I Chiang (International Journal of Informatics and Information Systems, 2021)
There are more and more applications and services of Cloud technology. Whether the government, enterprises or organizations, even everyone may have requirements of constructing cloud systems. To build the virtual cloud infrastructure VMware vSphere which is the leader of the information industry on virtual platforms can let users use Virtual Desktop Infrastructure by their mobile device. This study integrated some management programs such as Activity Directory, VMware vCenter, View connection server, VMware vSphere and used the shared storage system of FreeNAS to provide the cloud virtual environment to users. With the simple interface to manage, it successfully provides administrators to build Virtual Desktop Infrastructure faster. Users can use their own device to control the virtual desktop in a mobile classroom by VMware Horizon View or browser. Users can also use a shared storage system to be the information exchange platform. If you can connect to the Internet, you can use your own virtual desktop anywhere. Finally, the complete construction implements the combination of several operating systems and improves their performance to save lots of hardware cost. It also meets the social focus of carbon reduction and environment protection to achieve sustainable use.